Inertia Enhancement of an Isolated DC Microgrid Using Hierarchical Virtual Inertia Control. Issue 5 (3rd September 2022) - Samanta, Soumya; Mishra, Jyoti Prakash; Roy, Binoy Krishna
ABSTRACT: In this paper, a hierarchical virtual inertia control technique for a bidirectional DC–DC converter is proposed to enhance inertia of an isolated DC microgrid through the DC bus voltage regulation. The transient and steady-state performance of the DC microgrid, in terms of the DC bus voltage regulation, is enhanced with the implementation of the proposed hierarchical virtual inertia control. The DC microgrid is simulated under the variation of both source and load to verify the effectiveness of the proposed control technique. The results show that the DC bus voltage profile is improved during both transient and steady-state operation.